Mammies to Zombies: The Evolution of the “Magical Negro” and Racial Stereotyping in Film (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
"Mammies to Zombies" analyzes the evolution of racial stereotyping in film, specifically re-evaluating the role and origin of the "magical negro." Beginning with The Birth of a Nation and ending with Black horror, the paper compares the fetishization of Black bodies in film with the primitivization of Black culture that permeates the struggle for autonomy in representational media.For additional context, listen to the author's reflection on the piece below.